European Modernity and the Passionate South Gender and Nation in Spain and Italy in the Long Nineteenth Century - Andreu-Miralles, Xavier; Bolufer-Peruga, Mónica (Brill, 2022)
In the long nineteenth century, dominant stereotypes presented people of the Mediterranean South as particularly passionate and unruly, therefore incapable of adapting to the moral and political duties imposed by European civilization and modernity. This book studies, for the first time in comparative perspective, the gender dimension of a process that legitimised internal hierarchies between North and South in the continent. It also analyses how this phenomenon was responded to from Spain and Italy, pointing to the similarities and differences between both countries. Drawing on travel narratives, satires, philosophical works, novels, plays, operas, and paintings, it shows how this transnational process affected, in changing historical contexts, the ways in which nation, gender, and modernity were imagined and mutually articulated.